The role of magnesium in the pathogenesis of osteoporosis - Liu, Lin; Luo, Pan; Wen, Pengfei; Xu, Peng (Frontiers in Endocrinology, 2024)
Magnesium (Mg), a nutritional element which is essential for bone development and mineralization, has a role in the progression of osteoporosis. Osteoporosis is a multifactorial disease characterized by significant deterioration of bone microstructure and bone loss. Mg deficiency can affect bone structure in an indirect way through the two main regulators of calcium homeostasis (parathyroid hormone and vitamin D). In human osteoblasts (OBs), parathyroid hormone regulates the expression of receptor activator of nuclear factor-κ B ligand (RANKL) and osteoprotegerin (OPG) to affect osteoclast (OC) formation. In addition, Mg may also affect the vitamin D3 -mediated bone remodelling activity. vitamin D3 usually coordinates the activation of the OB and OC. The unbalanced activation OC leads to bone resorption. The RANK/RANKL/OPG axis is considered to be a key factor in the molecular mechanism of osteoporosis. Mg participates in the pathogenesis of osteoporosis by affecting the regulation of parathyroid hormone and vitamin D levels to affect the RANK/RANKL/OPG axis. Different factors affecting the axis and enhancing OC function led to bone loss and bone tissue microstructure damage, which leads to the occurrence of osteoporosis. Clinical research has shown that Mg supplementation can alleviate the symptoms of osteoporosis to some extent.